Reusing Natural Experiments - HEATH, DAVIDSON; RINGGENBERG, MATTHEW C.; SAMADI, MEHRDAD; WERNER, INGRID M. (Journal of Finance, 2023)
ABSTRACT After a natural experiment is first used, other researchers often reuse the setting, examining different outcome variables. We use simulations based on real data to illustrate the multiple hypothesis testing problem that arises when researchers reuse natural experiments. We then provide guidance for future inference based on popular empirical settings including difference‐in‐differences, instrumental variables, and regression discontinuity designs. When we apply our guidance to two extensively studied natural experiments, business combination laws and the Regulation SHO pilot, we find that many results that were statistically significant using single hypothesis testing do not survive corrections for multiple hypothesis testing.